Purification of Papain from Unclarified Papaya Juice using Reversed Phase Expanded Bed Adsorption Chromatography (RP-EBAC) - Chong, Fui Chin; He, Yu Hai; Syed Mohd Saufi, Tuan Chik (Elsevier, 2014)
The purification of papain using a reversed phase expanded bed adsorption chromatography (RP-EBAC)using a FastlineTM 10 EBAC column packed with AmberliteTM XAD7HP has been carried out in this study. An efficient large scale direct recovery of papain was developed and optimized from unclarified papaya juice feedstock in batch adsorption system. Enhancement of papain purity was further investigated in EBAC by stepwise elution strategy. High papain purity of 74.98% and high purification factor of 7.04 were obtained. This study shows a great potential of using two step elution RP-EBAC system to purify papain from unclarified papaya juice.